Giocare è una cosa seria: La qualità dell’organizzazione degli spazi per la qualità della scuola - Conti, Paola (Chimica nella Scuola, 2025)
Play is a powerful educational machine. Perhaps the most important, in the age range of 3 to 6 years. Contemporary children find themselves living in a context that makes them play by prior enrollment, depriving them of the opportunity to experience through play, autonomies, roles, relationships, skills. Reflection on the organizational conditions of school play (space, time, materials) enable teachers to use the full potential of this device for the purpose of personal growth and development and learning.